Total and class-specific analysis of per- and polyfluoroalkyl substances in environmental samples using nuclear magnetic resonance spectroscopy - Camdzic, Dino; Dickman, Rebecca A.; Aga, Diana S. (Journal of hazardous materials letters, 2021)
•19Fluorine nuclear magnetic resonance (19F-NMR) spectra for 34 perfluoroalkyl substances (PFAS) collected.•Methodology shown to not have matrix effects in complex matrix, such as biosolids.•Patterns within and between classes of PFAS with different headgroups demonstrated.•Reference data for emerging and legacy contaminants added to scientific literature. This study reveals unique information that fluorine nuclear magnetic resonance (19F-NMR) spectroscopy provides in the analysis of per- and polyfluoroalkyl substances (PFASs). Our results demonstrate that the intensity of the terminal -CF3 signal can be used to determine the total PFASs regardless of headgroup. Characteristic chemical shifts of different classes of PFASs can also be observed, and are useful for differentiating between classes of PFAS. The NMR spectra of PFASs with ether linkages (e.g. GenX) show characteristic reference signals for both -CF2 and -CF3 signals that are useful for detection. Notably, 19F-NMR can differentiate between PFASs, non-PFAS, and F− ions, eliminating the need for sample clean-up even for complex samples. To illustrate this, the 19F-NMR spectra of perfluorooctane sulfonic acid (PFOS) in biosolids extract and in clean solvent spiked with PFOS standard were compared, and showed a difference of < 0.3 % in their signal intensities. The lack of matrix effect is contrary to the suppression or enhancement observed in PFAS analysis by liquid chromatography with mass spectrometry, the most commonly used method for quantifying PFASs. This paper presents 19F-NMR reference spectra for 34 PFASs and discusses the complementarity of this method with other approaches for the total and class-specific analysis of PFASs.